A Silk Fibroin Nanoparticle Hydrogel Loaded With NK1R Antagonist Has Synergistic Anti‐Inflammatory and Reparative Effects on Dry Eye Disease - Bo Gong; Yi Liu; Huan Li; Xueming Ju; Dongfeng Li; Yuhao Zou; Xiaoxin Guo; Kai Dong; Jialing Xiao; Weijia Wu; Renjie Chai; Ruifan Zhang; et al. (Advanced Science)
Abstract Dry eye disease (DED) is a multifactorial illness affecting tears and the ocular surface. The neurokinin 1 receptor (NK1R) is a target for controlling T helper 17 (Th17) and regulatory T cell (Treg) imbalances. This work creates a silk fibroin (SF) nanoparticle hydrogel that targets NK1R with CP‐99,994 (CP). Combining CP and SF to generate stable nanoparticles while integrating a flexible hydrogel material results in a sustained‐release ophthalmic drop formulation (SF@CP@Gel), which provides a long‐lasting ocular formulation with anti‐inflammatory and reparative properties. SF@CP@Gel could maintain a stable CP concentration for 25 h with detectable biological activity. The cell counting kit‐8 and 2,7‐DHL‐DA results reveal that SF@CP@Gel has no cytotoxic effect on human corneal epithelial cells (HCECs) and decreases the reactive oxygen species level in oxidatively damaged HCECs. Cell scratch assays demonstrate that SF@CP@Gel can greatly increase HCEC migration and proliferation within 24 h. Furthermore, in vivo therapy with topical SF@CP@Gel twice daily markedly reduce clinical symptoms by reducing the amount of pathogenic Th17 cells while efficiently restoring Treg activity. In summary, this work reveals that SF@CP@Gel might attenuate DED by inhibiting NK1R‐mediated SP signaling and thereby modulating the Th17/Treg ratio, a potential anti‐inflammatory and repair treatment method for DED.